Reducing Human-Bear Conflicts: Bear-Resistant Trash Cans - Ethan T. Noel; Elizabeth F. Pienaar; Mike Orlando (EDIS)
The Florida black bear (Ursus americanus floridanus) is the only species of bear in Florida, with an estimated population of approximately 4,030 bears. Bears that eat garbage put themselves in danger. This 3-page fact sheet written by Ethan T. Noel, Elizabeth F. Pienaar, and and Mike Orlando and published by the Wildlife Ecology and Conservation Department explains how to secure human garbage from bears so that they don’t become reliant on human food sources, a condition that puts them at great risk of being killed from vehicle collisions, illegal shooting, or euthanasia.http://edis.ifas.ufl.edu/uw429